Empirical analysis of sexual recidivism - Lukić Natalija (Anali Pravnog Fakulteta u Beogradu)
The paper empirically examines relation of some static factors to recidivism among sexual offenders. The research sample consists of data gathered from personal files of 82 convicted persons who are either currently in the prison in Sremska Mitrovica or who have already served their sentences. Some of the hypotheses of the research have been confirmed. Firstly, a link between age at initial offending against sexual freedom and sexual recidivism is found to be statistically significant. Moreover, sexual recidivism is associated with the type of first criminal offense against sexual freedom - there are greater chances for recidivism if the first crime is less serious (prohibited sexual acts). Lastly, sexual offenders generally commit the same type of crimes against sexual freedom and this link is statistically significant. It is possible to make a clear distinction between two groups of recidivists - those who choose to victimize children and juveniles and those whose victims are adults. On the other hand, early onset of criminal career is not found to be statistically important. The same is concluded for marital and socio-economic status as well as for the history of rule violation (except sex crimes).